On the generic allocation of "Aligena" Pisum dall, 1908 - Güller, Marina (2011)
Aligena pisum Dall, 1908 is currently only known from the original description. The species was reported either under the lasaeid genus Aligena or the thyasirid genus Axinulus, and also regarded as a nomen dubium. Based on the re-examination of the holotype and the study of additional specimens from the Magellan Strait, Beagle Channel, and Southern Chile, the species is redescribed, properly illustrated, and its generic placement revised. The morphological and anatomical characters studied here reveal that the species is actually a thyasirid, and the presence of granules at the hinge plate is the main character supporting the reallocation of this species into the genus Adontorhina. The present finding provides the first record of Adontorhina in the Southern hemisphere.